2020
DOI: 10.1074/mcp.ra120.002163
|View full text |Cite
|
Sign up to set email alerts
|

FYN and ABL Regulate the Interaction Networks of the DCBLD Receptor Family

Abstract: The Discoidin, CUB, and LCCL domain-containing protein (DCBLD) family consists of two type-I transmembrane scaffolding receptors, DCBLD1 and DCBLD2, which play important roles in development and cancer. The non-receptor tyrosine kinases FYN and ABL are known to drive phosphorylation of tyrosine residues in YXXP motifs within the intracellular domains of DCBLD family members, which leads to the recruitment of the Src homology 2 (SH2) domain of the adaptors CT10 regulator of kinase (CRK) and CRK-like (CRKL). We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…Previous in vitro experiments reveal that the DCBLD1 interactome consists mainly of adaptor proteins and proteins associated with actin dynamics 15 , further implicating a role for DCBLD1 in focal adhesions and supporting the idea that DCBLD1 is a NRP-like protein. Both NRP1 and NRP2 are involved in focal adhesions: NRP1 regulates focal adhesion turnover and NRP2 regulates α6β1 integrin association with the cytoskeleton 11 , 34 .…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Previous in vitro experiments reveal that the DCBLD1 interactome consists mainly of adaptor proteins and proteins associated with actin dynamics 15 , further implicating a role for DCBLD1 in focal adhesions and supporting the idea that DCBLD1 is a NRP-like protein. Both NRP1 and NRP2 are involved in focal adhesions: NRP1 regulates focal adhesion turnover and NRP2 regulates α6β1 integrin association with the cytoskeleton 11 , 34 .…”
Section: Discussionmentioning
confidence: 62%
“…The intracellular region of DCBLD1 contains seven highly conserved YxxP motifs that are involved in phosphorylation-dependent binding to the CRKL signaling protein 14 . The Abl and Fyn kinases are responsible for this phosphorylation 14 , 15 . Phosphoprotemic bioinformatic analysis showed that the phosphorylation of four of these YxxP sites was altered following the inhibition of EGFR and MET and following HGF and FGF2 stimulation, suggesting an association of DCBLD1 with receptor tyrosine kinases 2 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reported literature has revealed that DCBLD2 influences the emergence and progression of multiple diseases, including cancer ( Kikuta et al, 2017 ; He et al, 2020 ; Alhamoudi et al, 2021 ; Coppo et al, 2021 ; Feng et al, 2021 ). Moreover, DCBLD2 has been found to interact with the receptor tyrosine kinases EGFR, VEGFR, PDGFR, and INSR ( Nie et al, 2013 ; Feng et al, 2014 ; Schmoker et al, 2019 ; Schmoker et al, 2020 ). Currently, no study has investigated whether DCBLD2 regulates the immune microenvironment and pathogenesis of tumors from the pan-cancer landscape.…”
Section: Discussionmentioning
confidence: 99%